Boko Haram: The Development of a Militant Religious Movement in Nigeria Boko Haram: Die Entwicklung einer militanten religiösen Bewegung in Nigeria - Roman Loimeier (Africa Spectrum, 2012)
Since 2009, the radical Muslim movement in northern Nigeria known as Boko Haram has become widely known in Western media for both its militant actions and its ultra-fundamentalist programme. This analysis examines Boko Haram from a historical perspective, viewing the movement as a result of social, political and generational dynamics within the larger field of northern Nigerian radical Islam. The contribution also considers some of the theological dimensions of the dispute between Boko Haram and its Muslim opponents and presents the different stages of militant activity through which this movement has gone so far. The article shows that movements such as Boko Haram are deeply rooted in northern Nigeria’s specific economic, religious and political development and are thus likely to crop up again if basic frame conditions such as social injustice, corruption and economic mismanagement do not change. Seit 2009 wurde die unter dem Namen Boko Haram bekannte radikale muslimische Bewegung in Nordnigeria in westlichen Medien für ihre militanten Aktionen und ihr ultrafundamentalistisches Programm bekannt. Der vorliegende Beitrag untersucht die Bewegung aus historischer Perspektive und sieht die Entstehung von Boko Haram als Ergebnis sozialer, politischer und generationsbezogener Dynamiken innerhalb des radikalen Islam im Norden Nigerias. Der Autor verweist zudem auf theologische Dimensionen der Auseinandersetzung zwischen der Bewegung und ihren muslimischen Gegnern und stellt die verschiedenen Phasen militanter Aktionen Boko Harams dar, die bislang erkennbar sind. Der Beitrag belegt, dass Bewegungen wie Boko Haram tief in den spezifischen ökonomischen, religiösen und politischen Bedingungen im Norden Nigerias verwurzelt sind und daher immer wieder entstehen können, sollten sich wesentliche Rahmenbedingungen – wie soziale Ungerechtigkeit, Korruption und ökonomisches Missmanagement – nicht ändern.